P is for peril ebook - Grafton, Sue (Kinsey Millhone, 2008)
Kinsey Millhone ventures into the darker side of the human soul in this gripping novel from #1 New York Times bestselling author Sue Grafton. Kinsey Millhone never sees it coming. She is mired in the case of a doctor who disappeared, his angry ex-wife, and beautiful current one—a case that is full of unfinished business, unfinished homes, and people drifting in and out of their own lives. Then Kinsey gets a shock. A man she finds attractive is hiding a fatal secret—and now a whole lot of beauty, money, and lies are proving to be a fatal distraction from what Kinsey should have seen all along: a killer standing right before her eyes...